THE INFLUENCE OF CELEBRITY ENDORSERS, BRAND IMAGE, AND BRAND TRUST ON PURCHASING DECISION OF WARDAH LIGHTENING SERUM AMPOULE PRODUCTS IN SURABAYA - Sekar Arum Tian Maulidya; Supriyono Supriyono (Yayasan Education and Social Center, 2023)
In an increasingly competitive marketing era, cosmetic companies must have an effective marketing strategy to win the competition and achieve success. One strategy that cosmetic companies often use is the use of celebrity endorsers, messengers who are well-known and have a strong influence on consumers. This study aims to determine the influence of Celebrity endorsers, Brand Image, and Brand trust on Purchase Decisions at Wardah Lightening Serum Ampoule in Surabaya City. This type of research is quantitative, with sampling techniques using non-probability and purposive sampling techniques. The population and sample in this study were women aged at least 17 years in the East Surabaya City area who had used or purchased Wardah Lightening Serum Ampoule, with 105 respondents. This study uses the Smart-PLS programs. The results of the study show that: 1) Celebrity Endorser influences Purchase Decisions, 2) Brand Image influences Purchase Decisions, and 3) Brand Trust influences Purchase Decisions